Le double voyage : Paris-Athènes (1945‐1975) - Arnoux-Farnoux, Lucile (Mondes méditerranéens et balkaniques (MMB), 2021)
Cultural exchanges between France and Greece peaked during the three decades that spanned from 1945 to 1975, despite, or perhaps because of, the successive crises Greece had to contend with during this period, from the Civil War (1944-1949) to the military junta (1967-1974). Greek intellectual and artistic elites were still very much drawn to post-war Paris, where they found both refuge from the chaos that reigned in their native land and an opening on modernity. So, Greece came to Paris, a place where a new generation of artists got a chance to show their work, where Greek architects made a name for themselves, often starting off with a job in Le Corbusier's studio, and where Greek literature was translated into French like never before. However, this was a journey in both directions, and France also went to Greece, where French ideas flourished, in art, literature and philosophy. The names of the people who undertook this journey back and forth, from one shore of the Mediterranean to the other, include Candilis, Dubuisson, Xenakis, Restany, Kessanlis, Aragon, Ritsos, Éluard, Kazantzakis, Sartre, Vassilikos, Milliex and many others.